2021
DOI: 10.2147/cmar.s343097
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Gene NPAS2 Act as a Putative Tumor Stimulative Factor for Uterine Corpus Endometrial Carcinoma

Abstract: Background: Mounting evidence indicates altered circadian rhythm represents a critical factor affecting carcinogenesis and tumor progression. The circadian gene neuronal PAS domain protein 2 (NPAS2) constitutes a newly discovered prognostic biomarker. NPAS2 dysregulation is found in multiple malignancies, although its functions in uterine corpus endometrial carcinoma (UCEC) remain largely unknown. Objective: To evaluate NPAS2's roles in UCEC and to explore the underlying mechanisms. Methods: NPAS2 transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Zhao et al indicated that miR-381-3p overexpression could accelerate cell proliferation and colony formation, which further initiates renal tumor deterioration and poor prognosis ( Zhao et al, 2020 ). A gynecologic cancer-associated study also elucidated that miR-381-3p had a positive correlation with uterine corpus endometrial carcinoma ( Zheng et al, 2021 ). Furthermore, some studies showed that miR-381-3p was upregulated in glioma ( Li et al, 2016 ), osteosarcoma ( Li et al, 2016 ), synovial sarcoma ( Hisaoka et al, 2011 ) and epithelioid sarcoma ( Papp et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al indicated that miR-381-3p overexpression could accelerate cell proliferation and colony formation, which further initiates renal tumor deterioration and poor prognosis ( Zhao et al, 2020 ). A gynecologic cancer-associated study also elucidated that miR-381-3p had a positive correlation with uterine corpus endometrial carcinoma ( Zheng et al, 2021 ). Furthermore, some studies showed that miR-381-3p was upregulated in glioma ( Li et al, 2016 ), osteosarcoma ( Li et al, 2016 ), synovial sarcoma ( Hisaoka et al, 2011 ) and epithelioid sarcoma ( Papp et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of the BMAL1/NPAS2 heterodimer is associated with high levels of the c-Myc gene in cells, leading to genomic instability and an increase in tumorigenesis [ 131 , 132 , 133 , 134 ]. Thus, the overexpression of NPAS2 is present in different types of cancer, indicating that the same mechanism could also occur in leukemia [ 135 , 136 , 137 , 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al (29) found that g-glutamyl hydrolase (GGH) expression levels were associated with Th2 cell expression and low-killer cell infiltration of CD56 bright cells, a process that could drive UCEC progression. Zheng et al (30) found that NPAS2 could lead to UCEC via an increase in tumor immune cell infiltration. Liu et al (31) developed and validated a Treg-related risk signature (TRRS) to assess the prognosis of UCEC and reflect the immune status of UCEC; this TRRS was capable of predicting the prognosis of UCEC patients that allowed for personalized treatment to be provided.…”
Section: Discussionmentioning
confidence: 99%